LAJU SERANGAN PHOLADIDAE DAN TEREDINIDAE PADA BEBERAPA JENIS KAYU - Mohammad Muslich; Ginuk Sumarni; Nurwati Hadjib (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The Mollusca wood borers, normally found in Indonesian sea waters, are divided into two types, i.e. Pholadidae and Teredinidae. Both types have different characteristic nature of infestation to wood. This paper deals with a study on the borer infestation to seven tropical commercial wood species.The study was conducted at Rambut Island seashore (on Java Sea) using wood samples measuring 2.5 cm by 5.0 cm by 80.0 cm. The samples were randomly arranged at a raft and observed after 8, 7 and 12 months.The result reveal that after 12 months most of the samples were completely attacked by the Pholadidae and Teredinidae. However moderate borer infestation was shown by Eusideroxylon zwageri, which means that this species is relatively resistant to marine borers infestation. Meanwhile, the infestation rates of Pholadidae and Teredinidae are significantly different, and they have different characteristic